Folk use of plant resource at Madi valley of Chitwan District, Nepal - Bishokarma, B.K.; Kinsey, C.K.; Dangol, D.R.; Chaudhary, P. (Banko Janakari, 2007)
The purpose of this study was to compare the use of the forest plant resources and folk nomenclature in the two communities of the Madi valley a Chitwan District. The information was collected during 2001 from 83 households in Chirauli and 57 households in Dhikurbari using semi-structured questionnaires. The folk nomenclature and relative importance of the plant species for medicine, firewood, fodder and timber differ in the two communities were recorded. A total of 128 species were reported in use by both communities, out of which 64 were common to both communities. The plant species used only in Chirauli accounted for 44 and that in Dhikurbari are 20. Tharu community of Chirauli reported higher number of plant species for medicinal, fodder and forage, fuel wood and timber than that of migrated people of Dhikurbari. Banko Janakari Vol.15(2) 2005 pp28-33